The Flow of Analytical Thinking High Cognitive Level Students In Mathematics Problem Solving - Muniri Muniri; Choirudin Choirudin (STAI Hubbulwathan Duri, 2022)
Analytical thinking ability Students in understanding and solving problems have not been specifically evaluated. Teachers still do not know how students solve problems using the thought process analytical, so it is not easy to make improvements in determining the right learning strategy for the concept. Study this uncover plot think analytical cognitive level students in non-routine mathematics problem solving based on stages Polya use approach qualitative for investigating mental level student at SMAN 1 Ngunut Tulungagung. Data analysis about Miles and Huberman includes data reduction, data presentation, and withdrawal conclusion. Research results show plot cognitive level student analytical thinking tall in complete problem through Step Polya (1) Understanding problem: differentiate; mention by verbally known and asked; write with mathematical models, and explain the relationship. (2) Planning solution: Organizing; state problem to in a mathematical model, choose draft math, choose a solution strategy from problem mathematics with write on the sheet work, explain the need state return problem to in the mathematical model, able explain the concept and able explain the chosen strategy. (3) Do plan solution: use draft selected math in complete problem mathematics, use the chosen strategy in solution, explain results solution by what was asked, and (4) Seeing return solution: prove the solution right, the exciting conclusion from results solution.